2020
DOI: 10.1002/cbic.202000605
|View full text |Cite
|
Sign up to set email alerts
|

α‐Methylene‐β‐Lactone Scaffold for Developing Chemical Probes at the Two Ends of the Selectivity Spectrum

Abstract: The utilities of an α‐methylene‐β‐lactone (MeLac) moiety as a warhead composed of multiple electrophilic sites are reported. We demonstrate that a MeLac‐alkyne not only reacts with diverse proteins as a broadly reactive measurement probe, but also recruits reduced endogenous glutathione (GSH) to assemble a selective chemical probe of GSH‐β‐lactone (GSH‐Lac)‐alkyne in live cells. Tandem mass spectrometry reveals that MeLac reacts with nucleophilic cysteine, serine, lysine, threonine, and tyrosine residues, thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 40 publications
(56 reference statements)
0
17
0
Order By: Relevance
“…We have recently demonstrated that the multi-electrophilic MeLac warhead can probe protein nucleophiles of different types in the live cell proteome. 14 MeLac labels reactive cysteine, serine, threonine, tyrosine, lysine residues, and the N-terminal amino group through the Michael acceptor or the acyl carbon atom on the warhead (Scheme 1A). When protein nucleophiles react at the Michael addition site of MeLac, a characteristic hydrolyzed product of the β-lactone ring can be observed to verify the Michael addition mechanism, resulting in a mass increase of 568.32206 Da.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We have recently demonstrated that the multi-electrophilic MeLac warhead can probe protein nucleophiles of different types in the live cell proteome. 14 MeLac labels reactive cysteine, serine, threonine, tyrosine, lysine residues, and the N-terminal amino group through the Michael acceptor or the acyl carbon atom on the warhead (Scheme 1A). When protein nucleophiles react at the Michael addition site of MeLac, a characteristic hydrolyzed product of the β-lactone ring can be observed to verify the Michael addition mechanism, resulting in a mass increase of 568.32206 Da.…”
Section: Resultsmentioning
confidence: 99%
“…When protein nucleophiles react at the Michael addition site of MeLac, a characteristic hydrolyzed product of the β-lactone ring can be observed to verify the Michael addition mechanism, resulting in a mass increase of 568.32206 Da. 14 Although nucleophilic thiols, amines, and hydroxyls can all react via the Michael addition, protein adducts of the addition reaction are dominantly attributed to MeLac reacting to nucleophilic cysteines. 14 We used CuAAC to attach desthiobiotin-PEG3-azide to MeLacA-reacted proteins.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations